Islamic Development Bank (IDB), foreign aid and the challenges for sustainable development in Africa - Daud, Mustafa; Abdul Razak, Nor Azam (Center for Promoting Ideas (CPI), USA, 2011)
Foreign aid/development assistance involves the transfer of resources in whatever form from the developed countries or multilateral financial institutions like World Bank, IMF, Islamic Development Bank (IDB) etc. to less developed or developing countries for the purpose of promoting and stimulating their economies for growth and development. Unfortunately, most of these countries, especially the African countries are characterized by multiple problems such as bad leadership and governance, mismanagement and corruption, debt crisis, insufficient and poor infrastructure, chronic poverty etc.; and all these problems have continued to make nonsense of foreign aid’s judicious and optimal utilization and impact on their economies.However, considering the position and role of IDB over the years in the global economic development; this paper examined the developmental activities of IDB in Africa and some of the challenges for sustainable development.In line with the Financial Two Gap Model (Double Deficit Model) and also the Islamic economic principle of Wide Circulation of Wealth, this paper therefore argues that there are a lot of challenges confronting the continent, which the Bank could assist in resolving through its development assistance, especially in the Muslim populated countries i.e. African Muslim Countries (AMCs). Challenges like Human capital development (HCD), poverty alleviation, corruption and mismanagement, infrastructural development, and good governance among others have enormous implications for sustainable development in the continent. And hence, this paper recommends that IDB should give more attention and priority to growth promoting types of foreign aid like program aid, sectoral aid, technical assistance etc. rather than financial aid, which is often squander. Doing this would facilitate the development process and by extension the desire for sustainability in the continent.